Debussy, Bartók, Stravinsky: Korszakváltás Budapesten és Párizsban a második dekád végén - Karasszon, Dezső (Studia Litteraria, 2015)
A decisive turning point signalling the demarcation between the Romantic era and the so-called “modern music” is a symbolic date during the last year of the First World War, the day of Debussy’s death: 25th March, 1918. The Revue Musicale in Paris devoted a whole thematic issue to the significant composer as well as to the important date. The magazine’s sheet music supplement (“Tombeau de Debussy”) contained pages from his contemporaries. Béla Bartók paid his homage with a Hungarian folk song adaptation. We can approach the background against this extraordinary decision from several perspectives. What is of importance here is that his work mirrored the end of an era and the need for something new. Igor Stravinsky had a totally different attitude. He contributed to the supplement with a modern chorale which, owing to his personal methods, became one of his greatest masterpieces, the “Symphony for Wind Instruments.” After all, he, just like Bartók, also intended to set the foundations of a completely new era with its new acoustics, inspired by Debussy and his oeuvre.